Cooperation between the Russian Federation and NATO in the field of European security - Jović-Lazić Ana (Međunarodni Problemi, 2014)
Preserving stability in the wider region of Europe cannot be achieved without the cooperation of the European Union, the Russian Federation and NATO. Dialogue Union with Russia in the field of security is marked by the fact that the EU wants to build its own security and defense system, with a tendency to mainly rely on NATO operations during the planning and military development. Also, the EU is ready to propose a Russia to get involved in that system, to a certain extent. The goal of NATO is to maintain a key role in ensuring stability and security in Europe and the world. At the same time NATO shows a willingness to cooperate closely with the EU and to periodically consult with Russia through certain organs of NATO. Russia, however, insists that the European security should be provided through of its equal cooperation with NATO and the EU. The current Ukrainian crisis showed as a major challenge for European security since the end of the Cold War. It made clear that relations between Russia, the EU and NATO are increasingly characterized by misunderstanding, mistrust and confrontation, which can have very negative consequences for the preservation of peace and security in Europe. [Projekat Ministarstva nauke Republike Srbije, br. 179029: Srbija u savremenim međunarodnim odnosima: Strateški pravci razvoja i učvršćivanja položaja Srbije u međunarodnim integrativnim procesima - spoljnopolitički, međunarodni ekonomski, pravni i bezbednosni aspekti]